2021
DOI: 10.1021/acs.jmedchem.1c00706
|View full text |Cite
|
Sign up to set email alerts
|

Are Pt(IV) Prodrugs That Release Combretastatin A4 True Multi-action Prodrugs?

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information ABSTRACT: "Multi-action" Pt(IV) derivatives of cisplatin with combretastatin A4 (CA4) bioactive ligands that are conjugated to Pt(IV) by carbonate are unique because the ligand (IC 50 < 10 nM) is dramatically 1000-folds more cytotoxic than cisplatin in vitro. The Pt(IV)-CA4 prodrugs were as cytotoxic as CA4 itself, indicating that the platinum moiety probably plays an insignificant role in triggering cytotoxicity, suggesting that the Pt(IV)-CA4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…This has for instance been observed for some Pt( iv ) derivatives with combretastatin A4 bioactive ligands, where the metal was a thousand fold less cytotoxic than the organic moiety. 371 This, and the usually complex synthesis, overall limits the efficacy and clinical translation of multi-action complexes. By employing nanocarriers for combination therapies, these challenges can be addressed to some extent.…”
Section: Metallodrugs and Nanomedicinementioning
confidence: 99%
“…This has for instance been observed for some Pt( iv ) derivatives with combretastatin A4 bioactive ligands, where the metal was a thousand fold less cytotoxic than the organic moiety. 371 This, and the usually complex synthesis, overall limits the efficacy and clinical translation of multi-action complexes. By employing nanocarriers for combination therapies, these challenges can be addressed to some extent.…”
Section: Metallodrugs and Nanomedicinementioning
confidence: 99%
“…Combretastatin A-4 (CA4), an tubulin polymerization inhibitor that exhibits dramatically 1000-folds more cytotoxic than cisplatin, was conjugated with Pt(IV) ( 14 ). CA4 showed higher cytotoxicity than Pt(IV)-CA4 conjugates in vitro , while in vivo test showed that Pt(IV)-CA4 conjugates exhibited significantly enhanced tumor suppression and reduced acute toxicity (weight loss) in LLC-bearing mice ( Schmidt et al, 2021 ). Pt(IV)-bioactive ligand conjugates usually exerted synergistic anticancer activity via multi-action.…”
Section: Endo-stimuli-responsive Pt- and Ru-based Anticancer Drugsmentioning
confidence: 99%
“…1 H NMR (400 MHz, DMSO-d 6 ) δ 11.20 (s, 1H), 7.58 (d, J = 8.0 Hz, 1H), 7.45 (d, J = 8.2 Hz, 1H), 7.16 (d, J = 7.4 Hz, 1H), 6.99 (t, J = 7.5 Hz, 1H), 6.84 (d, J = 2.1 Hz, 1H), 6.55−5.92 (m, 6H). 13 Commercial Compounds. Cisplatin (S1166) and CRT0044876 (S7449) were purchased from Selleck Co., Ltd.…”
Section: I S C I S -D I a M M I N E D I C H L O R O -( 1 H -I N D O ...mentioning
confidence: 99%
“…1 H NMR (600 MHz, DMSO-d 6 ) δ 10.40 (s, 1H), 8.19 (dd, J = 19.6, 7.9 Hz, 2H), 7.30 (t, J = 7.9 Hz, 1H), 7.16 (s, 1H), 6.23−5.92 (m, 6H) 13. C NMR (101 MHz, DMSOd 6 ) δ 167.69, 135.11, 133.22, 131.61, 131.28, 128.62, 121.36, 120.27, 107.10.…”
mentioning
confidence: 99%